Procalcitonin as a Biomarker for a Bacterial Infection on Hospital Admission: A Critical Appraisal in a Cohort of Travellers with Fever after a Stay in (Sub)tropics - Hesselink, Dennis A.; Bosmans-Timmerarends, Hanna; Burgerhart, Jan-Steven; Petit, Pieter L.; van Genderen, Perry J. (Interdisciplinary Perspectives on Infectious Diseases, 2009)
Fever in a returned traveller may be the manifestation of a self-limiting, trivial infection but it can also presage an infection that can be rapidly progressive and lethal. We studied the diagnostic accuracy of procalcitonin (PCT) as a biomarker for a bacterial cause of fever in a cohort of 157 consecutive travellers with fever after a stay in the (sub)tropics. Elevated procalcitonin levels were observed not only in about 50% of travellers with proven bacterial infection, but also in a significant proportion of travellers with a likely infection. Using a cutoff point of 0.5 ng/mL, procalcitonin had a sensitivity of 0.52 and a specificity of 0.76 for a bacterial cause of fever on admission. Interestingly, only 1 out of 16 patients with a proven viral infection had a marginally elevated PCT concentration on admission, suggesting that an increased PCT level likely excludes a viral infection as the cause of fever. However, the diagnostic accuracy of this semiquantitative procalcitonin test for a bacterial cause of fever on admission is too poor to advocate its use in the initial clinical evaluation of fever in a setting of ill-returned travellers.